Charlotte and Emily Brontë - Chitham, Edward. author. aut Link
VI, 144 p.
Keywords: This new book on the Brontes concentrates on the way in which the literary interests and expressions of Charlotte and Emily were built up. It makes use of recent research into background and reading matter to investigate the development of the authors' poetry and novels.